Monitoring the change of agricultural areas in Al-Qassim region (KSA) using remote sensing technology and GIS (1973-2020) - Bahemdan, Nada Hamdan; Jamil, Abdlhamed Mohammed (Journal of natural sciences, life and applied sciences, 2022)
The study to shed light on the efficiency and possibility of employing remote sensing technology and geographic information systems in monitoring and analyzing the change in agricultural areas in the Al-Qassim region during forty-seven years divided into eight periods from 1973 to 2020 AD, and that is by studying its distribution, knowing the natural and human factors affecting it, and following up on its rates of change during the periods specified for the study. This study relied mainly on satellite data from the open source (Landsat) series, as well as on the topographic map, soil map, and aquifers map.To achieve the goal of the study, the descriptive analytical method was used in digitally processing satellite images, analyzing them and drawing conclusions from them, and offering appropriate solutions and recommendations. The quantitative method was also used in calculating their areas, the study came out with maps representing agricultural lands throughout the study area, and the direction of its distribution pattern was identified, then the study touched on the most prominent effects of natural and human factors on it. A number of classification methods were used to extract agricultural areas from satellite images, such as the controlled classification, the single class classification, the application of the NDVI index and the SAVI index, but the results of the classification of the single class were relied on to better match the extracted results with the original images. This study concluded several results, the most important of which is that the Al-Qassim region witnessed a clear change in the agricultural areas between 1973 and 2020, and the change varied between expansion and decrease, as it was found that the first and second period of the study witnessed a significant expansion in agricultural areas, Then the decrease resumed sequentially during the third period until the fifth period, then the agricultural fields expanded during the sixth and seventh period, then the decrease resumed in the eighth period, and this change was linked to the application of the laws of development plans.The results showed that the distribution of agricultural areas in the Al-Qassim region is not symmetrical, as agricultural fields were concentrated in the central range in the northwest direction towards the southeast direction, and this concentration was linked to the presence of deep aquifers next to the valleys and arable soils.The study recommended the importance of using remote sensing data (satellite images) in monitoring agricultural areas and vegetation cover, and conducting similar studies in the future to update data related to agricultural areas in the Al-Qassim region, which is predicted to change in the coming years.
Keywords: Remote sensing; Al-Qassim; single class classification; NDVI; SAVI